Acesso no contexto da ESF em um município do Vale Jequitinhonha-MG - Roberta Souto Rocha Faria (2014)
The access to health services is defined in different ways by different authors. This study adopted a concept of access that understand the service in its social/organizational dimension, as the insertion of users in the Family Health Strategy (FHS) and the ability of health professionals to address the needs of users between different care levels. This study has the objective comprehend the access to the primary health care from the FHS perspective of users and professionals from a county in the Jequitinhonha Valley -MG. A qualitative case study has been the chosen methodology for the present study. Data collection was conducted in two FHS teams from Diamantina, located in the Valley Jequitinhonha / MG. Thirteen health professionals, thirty users and three coordinators of the Primary Health Care (PHC) were the subjects. Data collection was conducted through individual semi-structured interviews and systematic observation. The Ethics and Research committee approved the study and the CNS 196/96 Resolutions terms have been complied with. A content analysis proposed by Bardin has been conducted from which two categories emerged. The access to the FHS: users and health care professionals perceptions. subdivided into four subcategories; and the strategies for its access: user embracement and solving capacity. The access preferably occurs via FHS despite geographical, economical and functional barriers. Geographical barriers are due to limited mobility and transportation; economical to the lack of resources allocated to the PHC that is (deprived) provided with supplies and medicine; and functional barriers because of the difficulty in attention flow and high spontaneous demand which complicates activity planning by PHC professionals. It was also observed that user embracement and solving capacity of the PHC professionals are the access improvement tools, health care continuity and health care comprehensiveness. The importance given to bonding, affection and empathy have become remarkable elements towards including patients into the services. The user acknowledges the professional who seeks to meet their demands in spite of the municipal network limitations. It is therefore concluded that access to heath services depends on several administrative attributes to reduce daily barriers. Even with those barriers, users recognise the FHS as a preferred health system gateway, and understand the difficulties of care continuity are mainly related to service providers and to the secondary and tertiary care.